Porfirio Díaz en la historiografía masónica mexicana - Flores Zavala, Marco Antonio (2015)
This article analyses the presence of General Porfirio Diaz in Mexican Masonic historiography, using the works of José María Mateos (History of Freemasonry in Mexico from 1806 to 1884), Richard Chism (A contribution to the Masonic history of Mexico) and Luis J. Zalce (Notes on the history of Freemasonry in Mexico, my reading and my memories). The line of questioning is basic: What documentary sources were used by the authors to write their texts? How did they examine the performance of General Diaz, as an actor of the regime or a brother Mason? Although these are elemental questions, together they elucidate the ways in which Freemasonry was written about in Mexico. The article comprises two sections: The first outlines a biography of General Diaz and the works that are defined as Mexican Masonic historiography are presented. The second section presents a description of the work and how it examined the presence of Diaz in Freemasonry.